Kinesiology of the musculoskeletal system foundations for rehabilitation - Neumann, Donald A.; Grosz, Claudia M.; Kelly, Elisabeth Roen; Kiefer, Craig L.; Martens, Kimberly (St. Louis, Missouri Elsevier, 2017)
With its focus on the normal and abnormal mechanical interactions between the muscles and joints of the body, this comprehensive, research-based core text provides a foundation for the practice of physical rehabilitation. It presents kinesiology as it relates to physical rehabilitation in a clinically relevant and accessible manner-and acts as a bridge between basic science and clinical management
Getting started -- Basic structure and function of human joints -- Muscle : the primary stabilizer and mover of the skeletal system -- Biomechanical principles -- Shoulder complex -- Elbow and forearm -- Wrist -- Hand -- Axial skeleton : osteology and arthrology -- Axial skeleton : muscle and joint interactions -- Miscellaneous topics in kinesiology -- Hip -- Knee -- Ankle and foot -- Kinesiology of walking -- Kinesiology of running.
Includes bibliographical references and index
Keywords: Applied kinesiology; Movement education; Musculoskeletal system .